Integrated analyses of miRNA and mRNA profiles in leukocytes and serums in traditional Chinese medicine (TCM)-defined Pi-qi-deficiency syndrome and Pi-wei damp-heat syndrome resulting from chronic atrophic gastritis - Leiming You; Shen Zhang; Ting'an Li; Xiaopu Sang; Kunyu Li; Wei Wang; Xinhui Gao; Jiarui Wu; Guangrui Huang; Ting Wang; Anlong Xu (BMC, 2021)
Abstract Background To investigate the microRNA (miRNA)-gene interactions underlying leukocyte functions and characteristics, especially the potential serum biomarkers, implicated in the traditional Chinese medicine (TCM)-defined Pi-qi-deficiency syndrome (PQDS) and Pi-wei damp-heat syndrome (PDHS) resulting from chronic atrophic gastritis (CAG). Methods Using RNA/miRNA-sequencing approach, compared with healthy control population, we identified the PDHS- or PQDS-specific miRNAs and genes in leukocytes or serums, especially the Zheng (syndrome)-specific miRNA-gene interactions, and further decoded their functions and pathways. Results Despite being the TCM-defined Zhengs resulting from the same disease of CAG, the Zheng-specific genes and miRNAs were not same. The PDHS-specific leukocyte genes were mainly involved in defense and immune responses, including NOD-like receptor signaling and several synapses-related pathways. The expression upregulation of PDHS-specific genes enriched in the neutrophil degranulation pathway, indicated the enhanced leukocyte degranulation activation. The PQDS-specific genes in leukocytes were implicated in inflammatory response, extracellular matrix (ECM) organization and collagen catabolism. They could be enriched in MAPK and IL17 signaling and helper T cell differentiation pathways, especially the pathways associated with cell-to-cell adhesion/junction and communication such as cell adhesion molecules, ECM organization and ECM-receptor interaction, probably contributing to the characteristics and functions of leukocytes. Also, the experimentally-supported miRNA-gene interactions, concerned with COL4A2, COL26A1, SPP1 and PROCR, were implicated in the regulation of pathways related to cell-to-cell adhesion/junction and communication, suggesting the potential roles of the PQDS-specific miRNA-gene interactions for the characteristic and functional changes of leukocytes. Interestingly, the PQDS-specific miRNAs in the serums and the corresponding leukocytes, seemed to have the common roles in contributing to the characteristics and functions of leukocytes. Importantly, the hsa-miR-122-5p could be a potential biomarker, capable of being contained and carried in plasma exosomes and much higher expression in both the leukocytes and corresponding serums in the CAG patients with PQDS rather than PDHS. Conclusions These results may provide new insights into the characteristic and functional changes of leukocytes in the two Zhengs, PDHS and PQDS, especially the miRNA-mediated gene regulation underlying leukocyte characteristics and functions, with potential leukocyte and serum biomarkers for future application in integrative medicine. Trial registration ClinicalTrials.gov, NCT02915393. Registered on September 17, 2016.